Emission trading schemes: potential revenue effects, compliance costs and overall tax policy issues - Pope, Jeffrey; Owen, Anthony David (Elsevier Science Ltd., 2009)
The case for the imposition of carbon (emission) taxes or tradable carbon permits in important tax jurisdictions is arguably strong, based upon the polluter pays principle first proposed by Pigou almost a century ago. This paper briefly reviews the arguments for and against these market-based instruments, and discusses their relative advantages and disadvantages in a practical context. In the case of Australia, the revenue effect of the proposed tradable carbon permits scheme is estimated to be A$11.5 billion in 2010-11. For comparison, this is roughly equivalent to a quarter of the revenue from the Goods and Services Tax. The paper focuses on three neglected aspects of climate change taxation discussion to date: how much tax revenue is likely to be raised, and the administrative and compliance costs of an emissions trading scheme, with particular reference to Australia. In discussing these issues, the paper draws upon selected and relevant international experience, particularly the European Union emissions trading scheme. The challenges of an emissions trading scheme, including integration with the existing tax system, particularly in an Australian context, are also discussed. The paper concludes by emphasising the key challenges and issues facing this 'ultimate externality' debate, particularly from a taxation policy perspective.